EFFECTS OF GRADED LEVELS OF TOASTED SUNFLOWER SEED MEAL ON NUTRIENT DIGESTIBILITY AND CARCASS CHARACTERISTICS OF GROWING RABBITS - Yusuf, A.A.; Agyo, B.; Isa, B.; Gambo, A.; Diftuffe, M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
An eight-week feeding trial was conducted on the effects of a graded level of toasted sunflower seed meal on the carcass and nutrient digestibility of growing rabbits using forty-five rabbits crossbred (New Zealand X Dutch), ranging from five to six weeks of age, with an average weight of 650.34 g. The rabbits were randomly assigned to five dietary treatments, with 9 rabbits per treatment and 3 rabbits per replicate, in a Complete Randomized Design. Each treatment diet contained 0, 5, 10, 15, and 20% TSSM in diets 1, 2,3,4 and 5, respectively. The parameters measured include proximate composition of toasted sunflower seed initial body weight, body weight and final body weight, live weight, dressed weight, Others are nutrient digestibility, such as dry matter (DM), Crude protein(CP), Crude Fiber (CF), Ether Extract(EE), Ash and nitrogen-free extract (NFE). The results for carcass characteristics indicated that there were no significant (p<0.05) differences among the treatment groups in live weight, slaughter weight, dressed weight and dressing percentage the values obtained ranged from 1010.80 to 1103.67g,920.80 to 1013.67,486.87 to 535.83 g and 48.13 to 52.22g respectively. However, the results for nutrient digestibility showed a significant (p<0.05) difference among treatment groups for crude protein, crude fiber, ether extract, ash, and nitrogen-free extract. Conclusively, inclusion of 20% FSSM in the diet of rabbits gave better results on the nutrient digestibility, and carcass characteristics of growing rabbits without any adverse effect.